Characterizing and analyzing the sustainability and potential of China's cities over the past three decades. (March 2022) - Wang, Chenxing; Quan, Yuan; Li, Xiaoyun; Yan, Yan; Zhang, Jing; Song, Wentao; Lu, Junchen; Wu, Gang
Highlights: Urban sustainability characterizing framework for China's cities based on SDGs. There is total 12 indicators for urban sustainability characterization. Dashboard visualizations provide insights into urban sustainability and potential. Energy, living standards and air quality may restrict sustainability in Beijing. Unreasonable use of energy and land maybe key unsustainability aspects in Wuhan. Abstract: China's cities have made substantial advances in sustainable development through the development of ecological-civilization cities and green cities. Characterization of the level, development potential, and future direction of sustainable urban development is complex, thereby necessitating social, economic, ecological environment, and resource indicators. Synthesizing these indicators in a logical manner requires a deep understanding of cities and Sustainable Development Goals (SDGs). Therefore, based on the existing classification framework of SDG indicators, this study develops an urban sustainability characterization framework and indicator system applicable to China's cities. We also quantify the potential for sustainable urban development, and the sustainability and sustainable potential of all China's cities are calculated over 1985–2015. The results not only show a significant increase in the sustainable development capacity of cities, but also a decrease in the spatial heterogeneity of cities. Overall, cities have been developing toward a more sustainable state. The proposed framework is also used to develop a dashboard of sustainability for individual cities. This research can help government decision makers and researchers understand the level and state of sustainable development of individual cities globally, as well as identify future directions and key indicators to improve their potential for sustainable development.